The An overview of patient knowledge of anesthesia procedures through informed consent in the Jatiwinangun Purwokerto Surgical Specialty Hospital's central surgical installation: English - Hari Perkasa, Tubagus; Nova Handayani, Rahmaya; Burhan, Asmat (Java Nursing Journal, 2023)
Background: The submission of informed consent aims to obtain evidence of consent that can document legal and ethical liability. Anesthesia procedures include pre-anesthesia, intra-anesthesia and post-anesthesia. Pre-anesthesia is a pre-anesthesia and sedation assessment, informed consent for anesthesia and sedation, giving premedication drugs if necessary, and instructing fasting before surgery. Purpose: This study was to determine the level of patient knowledge about anesthesia procedures through informed consent at the Central Surgical Installation of Jatiwinangun Purwokerto Special Surgical Hospital. Methods: This study used a quantitative descriptive design with a cross sectional approach. The sampling technique used consecutive sampling of 108 respondents. The measuring instrument used was a questionnaire sheet. Analysis test using univariate test. Results: The analysis showed that the most dominant age of respondents was in the range of 36-45 years (23.4%), with the last education having a high school background (35%) and male (59.3%). Conclusion: An overview of the patient's knowledge level about anesthesia procedures through informed consent in the central surgical installation of Jatiwinangun Purwokerto Special Surgical Hospital, the majority have a sufficient level of knowledge.